Linking Farmers, Healthy Foods, and Underserved Consumers: Exploring the Impact of Nutrition Incentive Programs on Farmers and Farmers' Markets - Lydia Oberholtzer; Carolyn Dimitri; Gus Schumacher (Journal of Agriculture, Food Systems, and Community Development, 2016)
The number of farmers' markets in the United States has increased rapidly over the last 20 years. They have begun to attract a great deal of attention for their potential to provide consumers in rural and urban "food deserts" with fresh fruits and vegetables. Incentive programs targeting federal nutrition benefit customers at farmers' markets are new and rapidly growing programs that seek to address the problems of access and affordability for these consumers, as well as enhance the viability of participating markets and farmers. This article relies on data from markets providing nutrition incentive programming in 2010 and a survey of participating farmers in order to study federal nutrition benefit and incentive usage at the markets and to provide preliminary results about the type of farmers and markets that might benefit most from incentive programming. The farmers' market data show that Supplemental Nutrition Assistance Program (SNAP) redemption has increased substantially (usually doubling or more annually) in markets offering incentives. The analysis of farmer surveys revealed that both farmer and market characteristics are important to the impact of incentives on participating farmer sales. Farmers who were more likely to report increased sales from incentives were those with a higher proportion of market gross sales accounted for by fruits and vegetables; who depend on individual farmers' markets for a higher percentage of farm sales; who sell products at small or medium-sized markets; or who are very satistifed with the implementation of incentive programming at their markets. As these are preliminary results of new programming, future research needs are addressed.